Indeks Kepuasan Masyarakat terhadap Kinerja Corporate Communication PT Mifa Bersaudara - Tengku Kaddhafi (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2025)
This research aims to measure the community satisfaction index regarding the performance of corporate communication at PT Mifa Bersaudara in West Aceh. Corporate communication is very important to be planned and executed with a strong concept so that the company's work has a strong impact on the surrounding community. The satisfaction index measurement is conducted quantitatively by distributing questionnaires to the surrounding community. Quantitative data were explored through in-depth interviews with key company stakeholders. The study results show that the community is very satisfied with the company's communication performance. This satisfaction is reinforced by the interview results, where community leaders can communicate directly with company employees, especially in the field of corporate social responsibility (CSR). Likewise, the field officers, the company places one facilitator in each village in the company's first ring to accompany the company's CSR programs at the village community level. On the other hand, it is also important for the company to build a strong work team in the field of corporate communication, especially during a crisis.